Inverse association between type 2 diabetes and hepatocellular carcinoma in East Asian populations - Huo, Jinlong; Xu, Yaxuan; Chen, Xingqi; Yu, Jie; Zhao, Lijin (Frontiers in Endocrinology, 2024)
Aims: This study aims tTo investigate the potential association between type 2 diabetes (T2D) and hepatocellular carcinoma (HCC) in East Asian populations using Mendelian randomization (MR) analyses.Methods: Bidirectional Mendelian randomization (MR) studies were conducted using summary statistics from genome-wide association studies (GWAS) related to T2D and HCC. The potential effects of confounders such as chronic hepatitis B, chronic hepatitis C, body mass index, and alcohol intake frequency were corrected using a multivariate MR study. Various MR methods, including the inverse variance weighted (IVW) approach, were used to estimate the associations between T2D and HCC.Sensitivity analysis and assessment of heterogeneity were performed to ensure the robustness of the results.In the forward MR study, the IVW approach of MR analysis suggested an inverse associationcausal relationship between T2D and HCC in East Asian populations, with a risk odds ratio of 0.8628 (95% confidence interval [CI], 0.7888-0.9438). Furthermore, even after adjusting for BMI, chronic hepatitis B, and alcohol intake frequency, this study still supports the inverse associationcausal relationship between T2D and HCC. Additional MR methods provided further support for this relationship. Sensitivity analysis and assessment of heterogeneity confirmed the robustness of the results. The reverse MR analysis in this study did not show a clear impact of genetic liability to HCC on reduced risk of T2D(OR=0.9788; 95% CI, 0.9061-1.0574).This study provides evidence of an inverse associationcausal relationship between T2D and HCC in East Asian populations using MR analysis. Further studies are warranted to validate these findings.